Comparative investigation of specific enzyme activities in the organs and tissues of the skin parasite Macrogyrodactylus congolensis (Monogenea: Gyrodactylidae) - Safaa Zaky Arafa; El-Sayed Kasem Abd El-Hady; Samir Ahmed El-Abbassy (Journal of Basic and Applied Zoology)
Abstract Background Macrogyrodactylus congolensis is a pathogenic skin parasite that infects the economically important fish Clarias gariepinus. Little is known about the physiology and histochemistry of M. congolensis. This study aims to investigate the localization of the enzymes alkaline phosphatase, acid phosphatase, adenosine triphosphatase, 5′-nucleotidase, and glucose-6-phosphatase activities within the main organs and tissues of M. congolensis. Results Using histochemical methods, the study revealed predominant positive enzyme reactivities throughout the body of M. congolensis, with each enzyme demonstrating distinct localization patterns across various organs and tissues. All five enzymes were detected in the intestine, testis, vesicula seminalis, and excretory canal. Nerve cells and cerebral region exhibited positive reactions for alkaline phosphatase, acid phosphatase, 5′-nucleotidase, and glucose-6-phosphatase. The subtegumental cells showed positive reactions only for alkaline phosphatase and acid phosphatase, implying a specialized function in the parasite’s protective mechanisms and host-parasite interaction. Compared to other gyrodactylids infecting the same host, M. congolensis exhibited more pronounced enzymatic activities. Conclusion The enzyme activities of alkaline phosphatase, acid phosphatase, adenosine triphosphatase, 5′-nucleotidase, and glucose-6-phosphatase were more prominent in most tissues and organs of M. congolensis. The localization and distribution patterns differed from those observed in other gyrodactylids infecting the same host, suggesting potential biological differences, such as variations in embryonic development. The study’s findings may help in developing treatments or management strategies in aquaculture, where skin parasites can significantly affect fish health and economic viability.